Socialhjälpstaten i staden : Privat och offentlig fattigvård i Göteborg 1890–1920 - Nilsson, Malin ; 0000-0002-6069-7108; Karlsson, Birgit (Scandia, 2025)
This paper sets out to discuss the relevance of the concept of the ”social help state” (socialhjälpstaten) within the framework of Swedish historiography by focusing on the organization of poor relief in Gothenburg between 1890 and 1920. Coined by Norwegian historian Anne Lise Seip in 1984, the term socialhjälpstaten has been used extensively in the study of early welfare institutions and provisions in the Nordic countries around the turn of the 20th century. Despite its widespread application in other Nordic countries, the concept has as of yet not gained traction in Sweden. This paper endeavors to explore the potential applicability of the term socialhjälpstaten in describing the Swedish context during the same period. A fundamental aspect of socialhjälpstaten is its perspective on the era as a separate period characterized by a distinct ideology and institutions. This is in contrast to viewing it as merely a transitional phase between a limited laissez-faire state of welfare provisions and the 20th-century Scandinavian welfare states. Our study suggests that this characterization corresponds well with the case of Gothenburg. The welfare system in Gothenburg was modeled after the Elberfeld system, which emphasized volunteerism, decentralization, and personalized assistance, all of which were implemented to varying degrees during our time period. The city’s social provisions were rooted in a distinct ideology of self-help and institutionalized cooperation between private and public organizations involved in poor relief. Gothenburg exemplified a typical mixed economy of welfare, where the philanthropic organization Allmänna hjälpföreningen administered much of the outdoor relief and offered voluntary labor focused on ”help-to-self-help” case work. Simultaneously, the municipality focused on indoor relief and would over time increasingly contribute to funding the outdoor relief. The Swedish poor law at the time offered considerable flexibility for local municipalities in terms of developing their own welfare provisions. Building on previous research, we suggest that the concept of socialhjälpstaten may aptly describe not only Gothenburg but also other Swedish urban areas at the time. Hence, we believe that this concept is relevant for teaching and researching the dynamic period around the turn of the 20th century in Sweden. Furthermore, the concept has the potential to highlight both the Nordic similarities and differences in this historical context.
Keywords: Socialhjälpstaten; Mixed economy of welfare; Elberfeld system; philanthropy; poor relief